2020
DOI: 10.3390/cells9102311
|View full text |Cite
|
Sign up to set email alerts
|

ER-to-Golgi Transport in HeLa Cells Displays High Resilience to Ca2+ and Energy Stresses

Abstract: One third of all human proteins are either transmembrane or soluble secretory proteins that first target the endoplasmic reticulum (ER). These proteins subsequently leave the ER and enter the Golgi apparatus via ER-Golgi intermediate vesicular structures. Live-cell imaging of cargos fused to fluorescent proteins (FPs) enables the high-resolution visualization and characterization of secretory transport processes. Here, we performed fluorescence time-lapse imaging to assess the Ca2+ and energy dependency of ER-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 77 publications
(128 reference statements)
0
7
0
Order By: Relevance
“…Since an abrupt, discontinuous Ca 2+ pattern was associated with CAEEE in PC12 cells (Figure 9), we tested the sarco-endoplasmic Ca 2+ ATPase (SERCA) inhibitor 2,5-Di-(t-butyl)-1,4-hydroquinone (BHQ) in NRK cells, which invokes a surge of cytoplasmic Ca 2+ for a few minutes until extrusion and other mechanisms restore the cytoplasm to near-basal levels (see below). We previously demonstrated that a combination of ATP and BHQ increased ER-to-Golgi transport of GFP-F M 4-GH in HeLa cells, though a mechanism was not pursued further (34). As shown in Figure 10A, at low micromolar concentrations for 2.5 hours, BHQ stimulated ER-to-Golgi transport by 5O% or more, while by 10 μM, the compound caused no significant effect on transport (and in many cells, caused visible cytopathic effects).…”
Section: Resultsmentioning
confidence: 99%
“…Since an abrupt, discontinuous Ca 2+ pattern was associated with CAEEE in PC12 cells (Figure 9), we tested the sarco-endoplasmic Ca 2+ ATPase (SERCA) inhibitor 2,5-Di-(t-butyl)-1,4-hydroquinone (BHQ) in NRK cells, which invokes a surge of cytoplasmic Ca 2+ for a few minutes until extrusion and other mechanisms restore the cytoplasm to near-basal levels (see below). We previously demonstrated that a combination of ATP and BHQ increased ER-to-Golgi transport of GFP-F M 4-GH in HeLa cells, though a mechanism was not pursued further (34). As shown in Figure 10A, at low micromolar concentrations for 2.5 hours, BHQ stimulated ER-to-Golgi transport by 5O% or more, while by 10 μM, the compound caused no significant effect on transport (and in many cells, caused visible cytopathic effects).…”
Section: Resultsmentioning
confidence: 99%
“…Since an abrupt, discontinuous Ca 2+ pattern was associated with CAEEE in PC12 cells (Figure 9), we tested the sarco-endoplasmic Ca 2+ ATPase (SERCA) inhibitor 2,5-Di-(t-butyl)-1,4hydroquinone (BHQ) in NRK cells, which invokes a surge of cytoplasmic Ca 2+ for a few minutes until extrusion and other mechanisms restore the cytoplasm to near-basal levels (see below). We previously demonstrated that a combination of ATP and BHQ increased ER-to-Golgi transport of GFP-FM4-GH in HeLa cells, though a mechanism was not pursued further (34). As shown in Figure 10A, at low micromolar concentrations for 2.5 hours, BHQ stimulated ER-to-Golgi transport by 50% or more, while by 10 µM, the compound caused no significant effect on transport (and in many cells, caused visible cytopathic effects).…”
Section: In Nrk Cells Distinct Ca 2+ Mobilization Patterns Determine Whether Alg-2 Enhances or Depresses Er Exportmentioning
confidence: 99%
“…Two different cancer cell lines were chosen to conduct experiments, the HeLa cervical cancer and the MDA-MB231 breast cancer cells. Our choice was guided by two reasons: ( i ) HeLa cells not only represent the most robust system to study Golgi structure (Ayala and Colanzi, 2016; Wortzel et al, 2017) and function (Rauter et al, 2020), but also provide continuity with prior work because all biophysical and functional studies that led to the discovery of the coupled GTPases at the Golgi were performed in this model; ( ii ) we and others have shown that transcriptional upregulation or post-transcriptional activation (Bhandari et al, 2015; Dunkel et al, 2012; Sasaki et al, 2015) of GIV (the ‘linker’ between the two GTPases; Figure 1A ) supports several aggressive tumor cell properties (of which, many were demonstrated in MDA-MB231 cells (Jiang et al, 2008; Lopez-Sanchez et al, 2015; Midde et al, 2018; Rahman-Zaman et al, 2018; Rohena et al, 2020; Wang et al, 2015; Wang et al, 2017)), including, invasion, matrix degradation, proliferation and survival (Aznar et al, 2016; Garcia-Marcos et al, 2015). Elevated expression of GIV has also been reported in a variety of solid tumors (Garcia-Marcos et al, 2015; Getz et al, 2019), both in primary tumors (Ghosh, 2015; Ghosh et al, 2016b) as well as in circulating tumor cells (Barbazan et al, 2016; Dunkel et al, 2018) have been shown to correlate with tumor aggressiveness and poor survival across cancers.…”
Section: Resultsmentioning
confidence: 99%